2022
DOI: 10.1063/5.0087299
|View full text |Cite
|
Sign up to set email alerts
|

Computational evolution of high-performing unfused non-fullerene acceptors for organic solar cells

Abstract: Materials optimization for organic solar cells (OSCs) is a highly active field, with many approaches using empirical experimental synthesis, computational brute-force approaches to screen candidates in a given subset of chemical space, or generative machine learning methods which often require significant training sets. While these methods may find high-performing materials, they can be inefficient and time-consuming. Genetic algorithms (GAs) are an alternative approach, allowing for the "virtual synthesis" of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…In each generation after this cycle, the molecules are evaluated using a fitness function to predict their performance. Previous work in our group used these algorithms to design organic photovoltaic materials and infer new design rules. Our most recent study designed unfused NFAs and the GA revealed interesting strategies such as the inclusion of vinylene bridges and broken conjugation backbones . With this evolutionary approach, chemical space can be searched quickly and efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…In each generation after this cycle, the molecules are evaluated using a fitness function to predict their performance. Previous work in our group used these algorithms to design organic photovoltaic materials and infer new design rules. Our most recent study designed unfused NFAs and the GA revealed interesting strategies such as the inclusion of vinylene bridges and broken conjugation backbones . With this evolutionary approach, chemical space can be searched quickly and efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Hutchison et al 134 discovered novel NFAs by screening 5426 NFAs using a genetic algorithm and various sequences, symmetry and building blocks were analyzed. PBDB-T-SF is used as the donor material for this study because of its strong absorption in UV and high-energy visible regions.…”
Section: Review Of ML In Osc Researchmentioning
confidence: 99%
“…This sequence of the A-D components also agrees with our understanding of the push-pull effect mentioned above. 25 So, it seemed to us that NFAs with an A-D-D ′ -D-A conguration might perform better than their corresponding A-D-A ′ -D-A counterparts in OSCs. To test this assumption, the central electron-accepting core (A') of the 2,2'-((2Z,2 ′ Z)-(((2,5-diuoro-1,4-phenylene)bis(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b:3,4b ′ ]dithiophene-6,2-diyl))bis(methanylylidene))bis(3-oxo-2,3dihydro-1H-indene-2,1-diylidene))dimalononitrile (DF-PCIC) molecule was replaced with different strongly conjugated and electron rich donor groups.…”
Section: Introductionmentioning
confidence: 99%
“…This sequence of the A–D components also agrees with our understanding of the push–pull effect mentioned above. 25…”
Section: Introductionmentioning
confidence: 99%